Structural development and tectonostratigraphic evolution of the Sylhet Trough (northeastern Bengal Basin) in the context of Cenozoic Himalayan Orogeny: Insights from geophysical data interpretation. (April 2022) - Abdullah, Rashed; Aurthy, Munta Rumman; Khanam, Farida; Hossain, Mohammad Moinul; Sayem, Abu Sadat Md
Abstract: The Sylhet Trough of the Bengal Basin in the northeastern Indian Plate had started to develop since the Late Mesozoic Gondwana break-up and subsequent onset of the Cenozoic Himalayan Orogeny. However, very little is known about evolution of the Cenozoic Sylhet Trough in response to the latter tectonic event. Therefore, we aim at providing insights into the nature of basement, variations in structural style, kinematics and possible timing of structural activation(s) and tectonostratigraphic evolution of the Sylhet Trough based on geophysical data interpretation. Results show that the Sylhet Trough is mostly underlain by an attenuated continental or oceanic crust, bounded by a NE-SW-trending geophysical feature in the northwest that corresponds to the boundary with the Precambrian continental crust. The overlying Cenozoic sediments show variations in style of deformations and can be divided into three structural domains. Domains 1 and 2 in the southeastern and northeastern parts of the Sylhet Trough, respectively, are characterized by anticlines that are highly deformed to the east and are mostly associated with west- or northwest-dipping reverse faults. However, the anticlinal trends are deviated from a generalized NS-orientation in the Domain 1 to a dominant NE-SW-orientation in the Domain 2. Many of these anticlines resemble positive flower structures, indicating possible impacts of regional transpression associated with the Dauki and Kaladan faults to the north and east; respectively. In contrast, the Domain 3 to the west shows NE-SW-trending extensional structures. A southward thickening of the Oligocene to Miocene pre-kinematic packages indicates an early episode of foreland basin subsidence, although there is no evidence of a major structural activation. Rather, the presence of the Pliocene syn-kinematic packages indicates a major structural reactivation in response to the E-W and N-S crustal shortening since the Pliocene. This younger episode of structural activation can be directly linked with the late Cenozoic subduction related processes of the Indian Plate to the north and to the east, which is also responsible for the transformation of the Sylhet Trough into a remnant ocean basin. This latter (i.e., Pliocene and onward) episode of crustal shortening played a significant role in structural trap formation and preservation of hydrocarbons in the Sylhet Trough. Highlights: We provide new insights into the structural development and tectonostratigraphic evolution of the Sylhet Trough. Our results shows that the style of deformation is not uniform through-out the trough. In the Himalayan foreland basin setting, major episode of basin subsidence was initiated during the Oligocene. A major tectonic switching occurred since the Pliocene and the trough was subjected to the E-W and N-S crustal shortening.